2001
DOI: 10.1007/s004380000358
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of SGS1 in DNA damage-induced heteroallelic recombination that requires RAD52 in Saccharomyces cerevisiae

Abstract: The SGS1 gene of Saccharomyces cerevisiae is homologous to the genes that are mutated in Bloom's syndrome and Werner's syndrome in humans. Disruption of SGS1 results in high sensitivity to methyl methanesulfonate (MMS), poor sporulation, and a hyper-recombination phenotype including recombination between heteroalleles. In this study, we found that SGS1 forms part of the RAD52 epistasis group when cells are exposed to MMS. Exposure to DNA-damaging agents causes a striking, Rad52-dependent, increase in heteroall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 19 publications
5
39
0
Order By: Relevance
“…The two models arise because the situation is more complex for Sgs1. The sgs1 mutation decreases the rates of conversion induced by genotoxic agents as compared with the wild-type responses (16,49) but increases that of untreated cells (37). Thus, Sgs1 plays both positive and negative roles in recombination, which may or may not be related to its role in the intra-S-phase checkpoint (19,50).…”
Section: Are Mus81͞mms4 Sgs1͞top3 and Srs2 Involved In Replication Ormentioning
confidence: 99%
“…The two models arise because the situation is more complex for Sgs1. The sgs1 mutation decreases the rates of conversion induced by genotoxic agents as compared with the wild-type responses (16,49) but increases that of untreated cells (37). Thus, Sgs1 plays both positive and negative roles in recombination, which may or may not be related to its role in the intra-S-phase checkpoint (19,50).…”
Section: Are Mus81͞mms4 Sgs1͞top3 and Srs2 Involved In Replication Ormentioning
confidence: 99%
“…A role for MUS81-MMS4 in recombination was implied from its functional overlap with SGS1-TOP3 ). In the yeasts, there is good evidence that the RecQ-Top3 complex functions in the HR pathway (Wu et al 1998(Wu et al , 2001Gangloff et al 1999;Onoda et al 2001;Maftahi et al 2002;Oakley et al 2002;Shor et al 2002;Laursen et al 2003;Hope et al 2005). The notion that MUS81 might act downstream of RAD51 was further suggested by the suppression of mus81 sgs1 synthetic-lethality by rad51 (Fabre et al 2002;Bastin-Shanower et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, loss of the SGS1 DNA helicase results in genome instability, including increased rates of mitotic and meiotic recombination, gross chromosomal rearrangements, and chromosome loss (Watt et al 1995(Watt et al , 1996Sinclair et al 1997;Yamagata et al 1998;Chakraverty and Hickson 1999;Myung et al 2001;Onoda et al 2001;Hickson 2003). In addition, sgs1 mutants are sensitive to high levels of DNA-damaging agents such as ultraviolet light (UV), methylmethane sulfonate (MMS) and hydroxyurea (HU) (Yamagata et al 1998;Mullen et al 2000) presumably because of their effects on DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…Like the yeast sgs1 disruptants that show an increased frequency of spontaneous recombination (Watt et al, 1996;Onoda et al, 2001), BLM 7/7 DT40 cells have a hyper-recombination phenotype resulting in increased frequencies in both SCEs and targeted genome integration (Imamura et al, 2001). Sonoda et al (1999) demonstrated that HR between sister chromatids is the primary mechanism for SCE in DT40 cells.…”
Section: Possible Involvement Of Wrn In Homologous Recombinationmentioning
confidence: 99%